IMPARTASI SPIRITUALITAS PEMUDA MELALUI PAWAI PASKAH DI GMIT JEMAAT EISLEBEN FATUMNANU - Nelci Nafalia Ndolu; Sefronia Liu (SEKOLAH TINGGI TEOLOGI STAR'S LUB LUWUK BANGGAI, 2020)
The Easter Parade is a routine church activity that demonstrates the story of misery, death, resurrection, and ascension of Jesus Christ. The aim is to awaken the congregation's memories of salvation committed by Jesus Christ. Specifically, it aims to impart the spirituality of the congregation. Through the parade, the congregation, especially church youths, are expected to have a religious orientation, seek God's wisdom, interact with others lovingly and believe in divine power and strength in their lives. This study aims to show the effect of the Easter march on youth spirituality in the Evangelical Christian Church in Timor, the Eisleben Fatu Manu Oinlasi Church, in 2019. The study was conducted with a quantitative approach. The sample in this study amounted to 40 youth. Research data were obtained using a questionnaire. Hypothesis testing uses simple linear regression analysis. The results showed the Easter parade in 2019 had a significant influence in imparting the spirituality of the youth of the Evangelical Masehi Church in Timor, the Eisleben Fatu Manu Church, amounting to 86.7%.